2015
DOI: 10.1097/mcg.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

Single Versus Double Balloon Enteroscopy for Small Bowel Diagnostics

Abstract: Performance of SBE and DBE appears to be similar in terms of diagnostic/therapeutic yield, insertion depths, procedure time, complete enteroscopy, failure rates, or adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 27 publications
6
63
1
6
Order By: Relevance
“…According to the limited published data regarding SBE, the diagnostic yield ranges from 58% to 70% [5,911]. A recent meta-analysis by Lipska et al comparing SBE and DBE showed no significant differences in diagnostic yield, therapeutic yield, insertion depth, procedure time, failure rate, and complication rate [5].…”
Section: Discussionmentioning
confidence: 99%
“…According to the limited published data regarding SBE, the diagnostic yield ranges from 58% to 70% [5,911]. A recent meta-analysis by Lipska et al comparing SBE and DBE showed no significant differences in diagnostic yield, therapeutic yield, insertion depth, procedure time, failure rate, and complication rate [5].…”
Section: Discussionmentioning
confidence: 99%
“…85,86 A recent systematic review and metaanalysis suggested similar performance of single-balloon enteroscopy and DBE in terms of diagnostic and therapeutic yield. 87 Initial series 88 reported a low diagnostic yield with spiral enteroscopy (33%), but a more recent prospective study reported a higher yield (57%-62%) and improved outcomes in terms of transfusion requirements, iron supplementation, and additional therapeutic procedures with spiral enteroscopy in patients with small-bowel disorders. 89 A modeled cost-minimization analysis of the management of small-bowel bleeding proposed BAE as the most cost-effective initial test after standard endoscopy if the goal is treatment or definitive diagnosis, as opposed to visualization alone.…”
Section: Role Of Vcementioning
confidence: 97%
“…Fujinon DBE is commercially available since 2003 and Olympus SBE since 2007. Numerous studies have been performed in search of the best method of device-assisted enteroscopy [912]. In addition, device-assisted enteroscopy also allows intubation of the Roux-en-Y afferent limb to perform ERCP, although success rates vary [6, 1317].…”
Section: Introductionmentioning
confidence: 99%